Leipziger Germanistik: Beiträge zur Fachgeschichte im 19. und 20. Jahrhundert - Öhlschläger, Günther (De Gruyter, 2013)
In a series of individual essays, this volume presents the important contributors and major trends in the field of German linguistics and literary studies at the University of Leipzig from the beginning of the 19th century to the middle of the 20th century. The volume, which addresses the broader context of the discipline's evolution during this period, is intended as a contribution to the history of German studies in Leipzig and, given the importance of the individual scholars discussed, to the history of German studies as a whole. Günther Öhlschläger, Hans Ulrich Schmid, Ludwig Stockinger undDirk Werle, Universität Leipzig.
Description based upon print version of record
Keywords: Electronic books; Aufsatzsammlung; Germanistik; Universität Leipzig; Geschichte; Universität Leipzig / Germanistisches Institut